2018 American Heart Association Focused Update on Pediatric Advanced Life Support: An Update to the American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care. Issue 23 (4th December 2018) - Duff, Jonathan P.; Topjian, Alexis; Berg, Marc D.; Chan, Melissa; Haskell, Sarah E.; Joyner, Benny L.; Lasa, Javier J.; Ley, Sondra J.; Raymond, Tia T.; Sutton, Robert M.; Hazinski, Mary Fran; Atkins, Dianne L.
Abstract : This 2018 American Heart Association focused update on pediatric advanced life support guidelines for cardiopulmonary resuscitation and emergency cardiovascular care follows the 2018 evidence review performed by the Pediatric Task Force of the International Liaison Committee on Resuscitation. It aligns with the International Liaison Committee on Resuscitation's continuous evidence review process, and updates are published when the group completes a literature review based on new published evidence. This update provides the evidence review and treatment recommendation for antiarrhythmic drug therapy in pediatric shock-refractory ventricular fibrillation/pulseless ventricular tachycardia cardiac arrest. As was the case in the pediatric advanced life support section of the "2015 American Heart Association Guidelines Update for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care, " only 1 pediatric study was identified. This study reported a statistically significant improvement in return of spontaneous circulation when lidocaine administration was compared with amiodarone for pediatric ventricular fibrillation/pulseless ventricular tachycardia cardiac arrest. However, no difference in survival to hospital discharge was observed among patients who received amiodarone, lidocaine, or no antiarrhythmic medication. The writing group reaffirmed the 2015 pediatric advanced life support guideline recommendation that either lidocaine or amiodarone may be used to treat pediatric patients with shock-refractory ventricular fibrillation or pulseless ventricular tachycardia.